Going from 3D to 1D: a 1D approach to common-envelope evolution - Bronner, Vincent A.; Schneider, Fabian; Podsiadlowski, Ph; Röpke, Friedrich (Astronomy and astrophysics, 2024)
The common-envelope (CE) phase is a crucial stage in binary star evolution because the orbital separation can shrink drastically while ejecting the envelope of a giant star. Three-dimensional (3D) hydrodynamic simulations of CE evolution are indispensable to learning about the mechanisms that play a role during the CE phase. While these simulations offer great insight, they are computationally expensive. We propose a one-dimensional (1D) model to simulate the CE phase within the stellar-evolution code MESA by using a parametric drag force prescription for dynamical drag and adding the released orbital energy as heat into the envelope. We computed CE events of a 0.97 M⊙ asymptotic giant branch star and a point-mass companion with mass ratios of 0.25, 0.50, and 0.75, and compared them to 3D simulations of the same setup. The 1D CE model contains two free parameters, which we demonstrate are both needed to fit the spiral-in behavior and the fraction of ejected envelope mass of the 1D method to the 3D simulations. For mass ratios of 0.25 and 0.50, we find well-fitting 1D simulations, while for a mass ratio of 0.75, we do not find a satisfactory fit to the 3D simulation as some of the assumptions in the 1D method are no longer valid. In all our simulations, we find that the released recombination energy is needed to accelerate the envelope and drive the ejection.
Gesehen am 14.06.2024